2010
DOI: 10.1002/bdra.20649
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and paternal risk factors for anorectal malformations: A Dutch case‐control study

Abstract: This study revealed potential risk factors for ARM, including fever during pregnancy, maternal overweight, use of multivitamins, paternal smoking, and occupational exposures, but a familial component seems important as well.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
92
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(104 citation statements)
references
References 35 publications
7
92
5
Order By: Relevance
“…The exact genetics, perhaps in combination with environmental facts, remain ill defined [19]. Environmental studies have implicated paternal cigarette smoking and exhaust fume exposure as well as maternal obesity and diabetes as possible risk factors [20][21][22]. In addition, maternal exposure to industrial cleaning agents, multivitamin use and first trimester pyrexia have been implicated, although some of these findings could not be replicated in follow-up studies [21,22].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The exact genetics, perhaps in combination with environmental facts, remain ill defined [19]. Environmental studies have implicated paternal cigarette smoking and exhaust fume exposure as well as maternal obesity and diabetes as possible risk factors [20][21][22]. In addition, maternal exposure to industrial cleaning agents, multivitamin use and first trimester pyrexia have been implicated, although some of these findings could not be replicated in follow-up studies [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…Environmental studies have implicated paternal cigarette smoking and exhaust fume exposure as well as maternal obesity and diabetes as possible risk factors [20][21][22]. In addition, maternal exposure to industrial cleaning agents, multivitamin use and first trimester pyrexia have been implicated, although some of these findings could not be replicated in follow-up studies [21,22]. ARM reported in a first-or second-degree relative was most noteworthy in increasing ARM risk [21,22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…44 Other studies reported no significantly increased risk for several of the same outcomes. 24,26,35,54 The evidence of an association with birth defects other than neural tube defects, congenital heart defects, and oral clefts is therefore limited, as most defects were only investigated in 1 or 2 populations, and results seemed to be inconsistent between the studies.…”
Section: Fever and Health Effects In The Childmentioning
confidence: 99%
“…In spite of the passed years the etiology of VACTERL association still remains a mystery for scientists [4] . Inherited factors, as well as environmental influences have been reported [5][6][7] .…”
Section: Introductionmentioning
confidence: 99%